((x-1)/3)-2=((x-5)/4)

Simple and best practice solution for ((x-1)/3)-2=((x-5)/4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((x-1)/3)-2=((x-5)/4) equation:


x in (-oo:+oo)

(x-1)/3-2 = (x-5)/4 // - (x-5)/4

(x-1)/3-((x-5)/4)-2 = 0

(x-1)/3+(-1*(x-5))/4-2 = 0

(4*(x-1))/(3*4)+(-1*3*(x-5))/(3*4)+(-2*3*4)/(3*4) = 0

4*(x-1)-1*3*(x-5)-2*3*4 = 0

x-24+11 = 0

x-13 = 0

(x-13)/(3*4) = 0

(x-13)/(3*4) = 0 // * 3*4

x-13 = 0

x-13 = 0 // + 13

x = 13

x = 13

See similar equations:

| 2x+18y=18 | | 3x-11=2x+33 | | 14-b=8 | | -4+3x=7x+x+14x-8x | | 65=-6-x | | 81=x+181 | | 6/10-2/100 | | V-10=-19 | | -4+3x=7x+x+14-8x | | 9a-6=8a+1 | | 2x+2x+x+3x+3=24 | | 2x+0=5y-0 | | 5x+6=9x+3+8x | | 7bf^4-7bk^4= | | 6u(-5u^4)=0 | | 2a-1=3(a+1)+7a+5 | | X+4+5x+3+4x=21 | | (y^-1/4)^1/6 | | 9-3v=0 | | 17x-36=12x+7 | | x+8=-72 | | 2(x-6)=3(x-4) | | y^(3/2)-10y | | 18=x/7 | | 66=1.5x | | -5(6y-6)-y=-3y(y-5) | | 16a^4+36a^3b-10a^2b^2= | | 5(7n-4)-3= | | -0.666+4w=-0.111 | | -7+4(1+5a)= | | 9xa+1=8a | | 2v^2(8v^2+6vb-5b^2)= |

Equations solver categories